Artificial Intelligence–Generated Deepfake Pornography: A Normative Analysis of Criminal Liability and Victim Protection in Indonesian Law - Decri Reza; Meria Utama; Henny Yuningsih (Ius Poenale, 2026)
The rapid development of artificial intelligence (AI) has facilitated the creation of deepfake pornography through non-consensual digital manipulation of a person’s image, raising significant legal and human rights concerns. This study aims to examine the adequacy of Indonesian positive law in addressing AI-generated deepfake pornography, analyze the construction of criminal liability under existing legal frameworks, and formulate normative recommendations to strengthen victim protection. This research employs normative juridical research using statutory and comparative approaches. Primary legal materials include the Pornography Law, the Electronic Information and Transactions Law, the Criminal Code, and the Personal Data Protection Law. Secondary materials consist of legal doctrines and scholarly publications. A comparative analysis of China’s regulation on deep synthesis technology is conducted to assess potential reform models relevant to Indonesia. The findings indicate that existing Indonesian legislation provides partial legal grounds for prosecuting deepfake pornography; however, none explicitly regulates AI-based digital manipulation. This results in interpretative ambiguity, challenges in proving criminal elements, and limitations in ensuring comprehensive victim protection. The absence of clear provisions regarding synthetic content, platform accountability, and algorithmic transparency weakens enforcement effectiveness. This study contributes to Indonesian legal scholarship by offering a doctrinal analysis of criminal liability in deepfake pornography cases and proposing a reform-oriented framework to enhance legal certainty, strengthen enforcement mechanisms, and protect victims’ dignity and privacy in the digital era.